Red Blood Cell BCL-xL Is Required for Plasmodium falciparum Survival: Insights into Host-Directed Malaria Therapies - Coralie Boulet; Ghizal Siddiqui; Taylah L. Gaynor; Christian Doerig; Darren J. Creek; Teresa G. Carvalho (Microorganisms, 2022)
The development of antimalarial drug resistance is an ongoing problem threatening progress towards the elimination of malaria, and antimalarial treatments are urgently needed for drug-resistant malaria infections. Host-directed therapies (HDT) represent an attractive strategy for the development of new antimalarials with untapped targets and low propensity for resistance. In addition, drug repurposing in the context of HDT can lead to a substantial decrease in the time and resources required to develop novel antimalarials. Host BCL-xL is a target in anti-cancer therapy and is essential for the development of numerous intracellular pathogens. We hypothesised that red blood cell (RBC) BCL-xL is essential for Plasmodium development and tested this hypothesis using six BCL-xL inhibitors, including one FDA-approved compound. All BCL-xL inhibitors tested impaired proliferation of Plasmodium falciparum 3D7 parasites in vitro at low micromolar or sub-micromolar concentrations. Western blot analysis of infected cell fractions and immunofluorescence microscopy assays revealed that host BCL-xL is relocated from the RBC cytoplasm to the vicinity of the parasite upon infection. Further, immunoprecipitation of BCL-xL coupled with mass spectrometry analysis identified that BCL-xL forms unique molecular complexes with human μ-calpain in uninfected RBCs, and with human SHOC2 in infected RBCs. These results provide interesting perspectives for the development of host-directed antimalarial therapies and drug repurposing efforts.